Od alabastronu do flakonu René Lalique'a? Kilka lingwistyczno-kulturologicznych uwag o naczyniach na wonności, pachnidła, zapachy, perfumy? = From alabastron to René Lalique's bottle? A few linguistic-culturological remarks on fragrances, scents and perfumes containers? - Węgorowska, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article is a linguistic-culturological reflection on the subject of names and descriptions of vessels in which various fragrant substances have been kept from the antiquity. Verbal exemplifications cited in the text show that these artefacts are permanently inscribed in the history of world cosmetics and they document human creativity and sensitivity.
Keywords: naczynie; wonności; język; kulturologia; nazwa; perfume vessels; fragrances; language; name; culturology